2016
DOI: 10.5301/tj.5000493
|View full text |Cite
|
Sign up to set email alerts
|

“There's no Reason why”: A Campaign to Raise Cancer Awareness among Adolescents

Abstract: Introduction Adolescents with cancer often experience a longer diagnostic delay than children, mainly because they take longer to go to a doctor. The Italian Society for Adolescents with Oncohematological Diseases (SIAMO) has launched an information campaign focusing on raising adolescents’ awareness of the importance of diagnosing cancer early. Methods The concepts of the campaign were developed by a scientific committee of clinicians, cancer patients and their parents, and marketing experts. The title of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The improvement in the services for adolescents in Italy may be at least partly because of the successful communication strategy of the AIEOP Committee on Adolescents, involving various initiatives to improve the scientific community's awareness, and educational projects designed for teenagers and their families. In particular, it is worth mentioning the campaign, ''There's no reason why'' (to improve awareness that cancers can occur in adolescence too), 30 the campaign #fattivedere (an Italian term with the dual meaning of ''Don't hide!'' and ''Get a check-up'') to help young people to interpret any symptoms they experience, seek medical advice, and arrive at an earlier diagnosis), 31 and the ''Winners' Cup'' (a football tournament for adolescents with cancer, or a history of cancer; in its third edition in 2019, young people from eight different European countries were involved).…”
Section: Discussionmentioning
confidence: 99%
“…The improvement in the services for adolescents in Italy may be at least partly because of the successful communication strategy of the AIEOP Committee on Adolescents, involving various initiatives to improve the scientific community's awareness, and educational projects designed for teenagers and their families. In particular, it is worth mentioning the campaign, ''There's no reason why'' (to improve awareness that cancers can occur in adolescence too), 30 the campaign #fattivedere (an Italian term with the dual meaning of ''Don't hide!'' and ''Get a check-up'') to help young people to interpret any symptoms they experience, seek medical advice, and arrive at an earlier diagnosis), 31 and the ''Winners' Cup'' (a football tournament for adolescents with cancer, or a history of cancer; in its third edition in 2019, young people from eight different European countries were involved).…”
Section: Discussionmentioning
confidence: 99%
“…Research is another key issue for programs dedicated to AYA. Several studies on AYA have been conducted by the INT Youth Project staff (some already published, others ongoing) on matters such as psychosocial support needs, epidemiology, clinical outcomes, and basic science studies on tumor biology across the age spectrum …”
Section: Discussionmentioning
confidence: 99%
“…Several studies on AYA have been conducted by the INT Youth Project staff (some already published, others ongoing) on matters such as psychosocial support needs, epidemiology, clinical outcomes, and basic science studies on tumor biology across the age spectrum. [16][17][18][19][20][21][22][23][27][28][29][30][31] The last parameter considered in our list concerned the community's recognition of the Youth Project's activities. The large number of articles published in the mass media and the numerous events/meetings in which the Youth Project's initiatives were presented and discussed may be seen as further proof of its effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that, although they are concerned about their own well-being, they often postpone reporting any symptoms they are experiencing to an adult, as other studies had previously reported (41, 42). Enlightened by the effective need to improve awareness, SIAMO launched two campaigns [#fattivedere – Italian term with a double meaning: “Don’t hide!” and “Get a check-up,” and “There is no reason why” (43)] targeted to reduce the diagnostic delay that AYA with cancer experience. Both of these campaigns were linked to the SIAMO website page that provides information on how to interpret symptoms.…”
Section: The Model Of the Youth Project Of Milanmentioning
confidence: 99%